Mobile Agent-Based Directed Diffusion in Wireless Sensor Networks. (2nd October 2006) - Chen Chen, Min Min; Kwon Kwon, Taekyoung Taekyoung; Yuan Yuan, Yong Yong; Choi Choi, Yanghee Yanghee; Leung Leung, Victor C. M. Victor C. M.
Abstract : In the environments where the source nodes are close to one another and generate a lot of sensory data traffic with redundancy, transmitting all sensory data by individual nodes not only wastes the scarce wireless bandwidth, but also consumes a lot of battery energy. Instead of each source node sending sensory data to its sink for aggregation (the so-called client/server computing), Qi et al. in 2003 proposed a mobile agent (MA)-based distributed sensor network (MADSN) for collaborative signal and information processing, which considerably reduces the sensory data traffic and query latency as well. However, MADSN is based on the assumption that the operation of mobile agent is only carried out within one hop in a clustering-based architecture. This paper considers MA in multihop environments and adopts directed diffusion (DD) to dispatch MA. The gradient in DD gives a hint to efficiently forward the MA among target sensors. The mobile agent paradigm in combination with the DD framework is dubbed mobile agent-based directed diffusion (MADD). With appropriate parameters set, extensive simulation shows that MADD exhibits better performance than original DD (in the client/server paradigm) in terms of packet delivery ratio, energy consumption, and end-to-end delivery latency.